2020
DOI: 10.1177/1464420720917175
|View full text |Cite
|
Sign up to set email alerts
|

Studies on cold metal transfer welding of aluminium alloy 6061-T6 using ER 4043

Abstract: Aluminium alloy 6061-T6 is utilized in aerospace industry for developing pressure vessel liner. Cold metal transfer is a promising welding process used in fabricating aluminium structures. The present work is focussed to achieve an optimum welding parameter for joining a 3.5-mm thick pressure vessel and to examine the mechanical properties and metallurgical nature of the weldment. The welded joint was evaluated as defect free using radiography test. The joint efficiency (66.61%) and measured microhardness of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Comparing CMT with other types of fusion welding, many researchers have confirmed that CMT has “colder” characteristics. The characteristics of CMT, with low heat input and less spatter, are highly suitable for welding age-hardening aluminum alloys that are easily affected by the welding temperature and cause serious deterioration in properties [ 4 , 154 , 155 , 156 , 157 , 158 ]. Cornacchia et al [ 159 ] comparatively studied CMT and MIG welding for a 3 mm EN AW-6005A-T6 with ER4043 filler wire, and the joint efficiency for CMT and MIG welding was 63.6% and 58.7%, respectively.…”
Section: Low-heat-input Weldingmentioning
confidence: 99%
“…Comparing CMT with other types of fusion welding, many researchers have confirmed that CMT has “colder” characteristics. The characteristics of CMT, with low heat input and less spatter, are highly suitable for welding age-hardening aluminum alloys that are easily affected by the welding temperature and cause serious deterioration in properties [ 4 , 154 , 155 , 156 , 157 , 158 ]. Cornacchia et al [ 159 ] comparatively studied CMT and MIG welding for a 3 mm EN AW-6005A-T6 with ER4043 filler wire, and the joint efficiency for CMT and MIG welding was 63.6% and 58.7%, respectively.…”
Section: Low-heat-input Weldingmentioning
confidence: 99%